Atomistic Description of Reaction Intermediates for Supported Metathesis Catalysts Enabled by DNP SENS. Issue 15 (8th March 2016) - Ong, Ta‐Chung; Liao, Wei‐Chih; Mougel, Victor; Gajan, David; Lesage, Anne; Emsley, Lyndon; Copéret, Christophe
Abstract: Obtaining detailed structural information of reaction intermediates remains a key challenge in heterogeneous catalysis because of the amorphous nature of the support and/or the support interface that prohibits the use of diffraction‐based techniques. Combining isotopic labeling and dynamic nuclear polarization (DNP) increases the sensitivity of surface enhanced solid‐state NMR spectroscopy (SENS) towards surface species in heterogeneous alkene metathesis catalysts; this in turn allows direct determination of the bond connectivity and measurement of the carbon–carbon bond distance in metallacycles, which are the cycloaddition intermediates in the alkene metathesis catalytic cycle. Furthermore, this approach makes possible the understanding of the slow initiation and deactivation steps in these heterogeneous metathesis catalysts. Abstract : Making SENS of a structure : Dynamic nuclear polarization surface‐enhanced solid‐state NMR spectroscopy (DNP SENS) was used to investigate the catalytic intermediates of a well‐defined tungsten alkylidene metathesis catalyst, which is present in low concentration at the surface of a silica support. The increase in NMR signal sensitivity permits determination of C−C connectivity and distance measurements, by a combination of 1D and 2D NMR techniques, on only a minute amount of surface sites.